Relative Earnings and the Demand for Unskilled Labor in West German Manufacturing - Viktor Steiner; Kersten Wagner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
We analyze the economic factors which have contributed to the dramatic decline of the employment share of unskilled labor in German manufacturing, in particular the role played by the relatively rigid earnings structure. Potential effects of intensified international competition and skill?biased technological change on the relative employment and earnings position of unskilled workers are also discussed. We find that the substitution elasticity between unskilled and skilled labor is rather low. The decline in the employment share of unskilled workers attributable to an inflexible earnings structure therefore seems to have been modest compared to the trend decline in the skills ratio. We also find some modest effects from international competition and technological change on the employment share of unskilled labor.
Keywords: J23; J31; 330; Lohnstruktur; Ungelernte Arbeitskräfte; Arbeitsnachfrage; Industrielle Beschäftigung; Facharbeiter; Faktorsubstitution; Deutschland